Recovery of conduction disorders after sutureless aortic valve replacement. (22nd January 2021) - Lam, Ka Yan; Timmermans, Naomi; Akca, Ferdi; Tan, Erwin; Verberkmoes, Niels J; de Kort, Kim; Soliman-Hamad, Mohamed; van Straten, Albert H M
Abstract: : OBJECTIVES: Conduction disorders and the need for permanent pacemaker (PPM) implantation after surgical aortic valve replacement are well-recognized complications. However, in the case of sutureless valve prostheses, it remains unknown whether pacemaker (PM) dependency and conduction disturbances resolve over time. Our aim was to evaluate whether conduction disorders after Perceval sutureless valve implantation recover during follow-up. METHODS: Patients undergoing isolated surgical aortic valve replacement or concomitant aortic valve replacement with coronary artery bypass surgery using the Perceval sutureless valve, between January 2010 and July 2018, were included. Postoperative electrocardiogram findings were analysed to determine the incidence of new-onset left bundle branch blocks (LBBBs) and the requirement for PPM implantation. During a postoperative period of 6–18 months, electrocardiogram findings during PM checks were analysed to determine PM dependency and LBBB persistence. RESULTS: Out of 184 patients who received a Perceval prosthesis during the study period, 39 (21.2%) patients developed new-onset LBBB and 10 patients (5.4%) received a PPM postoperatively. The occurrence of conduction disorders was not associated with valve size. Follow-up was completed in 176 (95.7%) patients. In patients with a new-onset LBBB, 35.9% recovered during follow-up ( P = 0.001). Seven out of 10 (70%) patients remained PM dependent. CONCLUSIONS: After Perceval aortic valve implantation, new-onset LBBB recovers in more than one-third of patients during follow-up. In patients who needed a postoperative PPM, the majority remained PM dependent.